The changing trends in university governance in Malaysia: Issues and challenges - Quddus, S M Abdul; Yusuff, Ahmad Sabri (Netinsearch International, 2017)
Society has undergone massive changes in its socioeconomic and cultural facets. Thus the concept of knowledge society has got momentum with it, with education being a key motivator of these changes. Following the introduction of the “Wawasan 2020” (Vision 2020) and the subsequent declaration of the Transformasi Nasional (TN50) policy, increasing attention has been made in the effort to change the structure of higher education governance in Malaysia (Dzulkifli, 2011). The ongoing reforms in University governance are driven by the notion that Malaysia aims to set themselves up as a central node for better education in the region (Quddus & Ahmad, 2015) and as a nation aims to transform into “a nation of calibre, with a new mindset” (New Straits Times, Online - 21 October, 2016). As a nation, Malaysia also wants to be fully developed in terms of economic development, ensuring social justice, a system of good governance, quality of life and to uphold social and spiritual values, political stability, national pride, confidence, unity and social cohesion in the polity (“The Way Forward—Vision 2020” speech delivered by Dr Tun Mahathir, Source: http://www.epu.jpm.my/ 02/28/1991). This paper explores whether these particular reform initiatives introduced in relation to higher education management would help to achieve the declared objectives of the government of Malaysia. In analysing the impact of reform initiatives on the production of knowledge in Malaysia, and across the globe, this paper has explored the answers of the following questions: a) What are the major changing trends of higher education governance in Malaysia; b) How current reform initiatives relating to university governance will affect the “soaring upwards” motto of the government i.e. the ministry of higher education; c) what are the current challenges of university governance in Malaysia and how to resolve them. The findings of this study reveal that there are many innovative programs and policies relating to higher education management in Malaysia, however some of them are not supportive of and to some extent even contradict the objectives of the government and society at large.